Clinical efficacy and mechanism of transcutaneous neuromodulation on ineffective esophageal motility in patients with gastroesophageal reflux disease. Issue 3 (18th October 2022) - Ma, Yimin; Cai, Rencheng; Liu, Zhengqing; Zou, Xiaoping; Qiao, Zhenguo
Abstract: Background: Esophageal motility disorder is one of the pathogenesis of gastroesophageal reflux disease (GERD). The clinical and functional relationship between the ineffective esophageal motility (IEM) and GERD have been found. PPI is a widely used drug of this diaease, but some patients have poor efficacy. The purpose of this study was to investigate the efficacy and possible mechanism of Transcutaneous Neuromodulation in these patients. Methods: Fifty‐six patients with GERD with IEM were enrolled and randomly divided into two groups, one group was TN ST‐36 group, the other group was sham TN group. The GERD questionnaire (GerdQ), quality of life score, MOS item short from health survey (SF‐36), Hospital Anxiety and Depression Scale (HADS) were used to assess the severity of symptoms. High‐resolution esophageal manometry (HRM) test was performed to assess low esophageal sphincter (LES) pressure and distal contractile integral (DCI). The heart rate variability (HRV) test was performed to assess autonomic nervous function. Key Results: Compared with sham TN, chronic TN treatment decreased the GERD‐Q score ( p < 0.001). The anxiety score ( p = 0.058) and depression score ( p = 0.156) were decreased, but there were no statistical differences. Chronic TN treatment also significantly improved the quality of life of patients, mainly in physical function, physical pain, overall health, vitality, social function, emotional function, and mental health. Acute TN treatment increased the DCI ( p < 0.001) and LES pressure ( p < 0.001) significantly and decreased the combined percentage of failed and weak peristalsis ( p < 0.001). Concurrently, acute TN enhanced vagal activity ( p < 0.001). Conclusions and Inferences: IEM is an important link in the pathogenesis of GERD. Chronic TN treatment can significantly improve the clinical symptoms of patients. Acute TN treatment can significantly increase LES pressure and DCI and reduce the frequency of esophageal lost peristalsis and weak peristalsis. The improvement of esophageal motility in GERD patients with IEM by TN treatment may be related to the regulation of autonomic nervous function. Abstract : Effects of acute Transcutaneous Neuromodulation (TN) ST36 on autonomic nervous function: After acute TN ST36 treatment, vagus nerve activity of enrolled patients (Ineffective esophageal motility in Patients with Gastroesophageal Reflux Disease) increased significantly, sympathetic nerve activity decreased significantly, and sympathetic vagus ratio also decreased significantly.